Contrasting composition of two biotite generations in the Lizhuang rare‐earth element deposit, Sichuan Province, Southwestern China. (17th June 2020) - Shu, Xiaochao; Liu, Yan; Li, Deliang
Abstract : Biotite is an important silicate mineral that can be used to decipher the physicochemical attributes of magmatic or hydrothermal systems. The Lizhuang rare‐earth element (REE) deposit in Sichuan Province, Southwestern China, formed from continuous magmatic‐hydrothermal processes is related to a Cenozoic carbonatite–syenite complex. Biotites are abundant in this deposit, which can be divided into two generations: generation I in intergrown with alkaline feldspar and aegirine‐augite and generation II in association with bastnäsite‐(Ce). We investigated chemical composition of the two biotite generations using electron‐microprobe(EMPA) and laser ablation–inductively coupled plasma–mass spectrometer (LA–ICP–MS) analyses to understand the development of REE mineralization. Generation I biotite has relatively high Al2 O3 (10.2–12.4 wt%), TiO2 (0.49–1.85 wt%), and FeOtot (12.2–15.9 wt%), but low SiO2 (40.0–42.5 wt%) contents compared to generation II counterpart. These two generations of biotite also differ in some key trace elements. Specifically, generation I biotite has much higher concentrations of Sr (up to 234 ppm) and Ba (up to 20, 796 ppm), but lower levels of Li (47.5–126 ppm) with respect to its generation II counterpart. When comparing Lizhuang biotites with those of other barren carbonatite complexes, we identified an unusual compositional trend in the generation II biotites termed as fluorphlogopite trend. This trend is marked by the continuous increase in the Mg content towards mineralization and, therefore, can serve as a diagnostic attribute in the determination of mineralized carbonatite complexes. Fluorine in biotite is an important parameter that can be used as a vector for REE exploration, because the generation II biotite presents much higher fluorine contents (2.20–4.06 wt%) than its generation I counterpart (0.87–1.59 wt%). The compositional data of the two biotite generations indicate a depletion of Fe and a progressive enrichment in Mg and F in the ore‐forming system during its evolutionary process. Physicochemical parameters estimated by biotite composition suggest that there is a trend of strongly decreasing temperature from the crystallization of generation I to generation II biotite. It is therefore concluded that temperature is a major factor favourable for REE mineralization in the Lizhuang deposit, particularly given related experimental studies. Taken together, we propose that biotite composition could serve as a proxy for REE mineralization processes and as a reliable index for REE routine exploration in a carbonatite‐related setting.